STUDY ON SOME SOMATIC AND PHYSICAL PARAMETERS OF PLAYMAKER IN WOMEN VOLLEYBALL - Sorin GRĂDINARU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
Major competitions in any sport allow methodists and technicians to analyse different aspects related to the features of a game from a physical, technical, and tactical perspective. Women volleyball tournament at the Olympic Games in London (2012) gathered only 12 teams, unlike other major competitions where there are more teams. The dramatic selection of the volleyball players after extremely tough qualification tournaments gathers the most valuable volleyball teams at a certain point in time. In this paper, the author draws a model of the game coordinator in women volleyball as seen at the Olympic Games in 2012. The author aimed at checking if the values of the parameters of game coordinators (age, height, weight, attack jump, block jump) have an impact on a team's yield and rank. The subjects of the research were game coordinators of the 12 volleyball teams in the Olympic Games of 2012. The research methods used are the study of literature, the statistics-mathematical method, and the graphic representation method. Thus, the average profile of a game coordinator is 27 years old, 178.37 m tall, 67.29 kg, attack jump 293.45 cm, block jump 281.45 cm. The first three volleyball teams had values below the means of these five parameters. The Olympic champion, the Brazilian team, has game coordinators whose parameters are below the mean values of the other competitors, which points out that these values are not relevant for the volleyball game coordinators' yield.